7+6n+4-3n=

Simple and best practice solution for 7+6n+4-3n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+6n+4-3n= equation:


Simplifying
7 + 6n + 4 + -3n = 0

Reorder the terms:
7 + 4 + 6n + -3n = 0

Combine like terms: 7 + 4 = 11
11 + 6n + -3n = 0

Combine like terms: 6n + -3n = 3n
11 + 3n = 0

Solving
11 + 3n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 3n = 0 + -11

Combine like terms: 11 + -11 = 0
0 + 3n = 0 + -11
3n = 0 + -11

Combine like terms: 0 + -11 = -11
3n = -11

Divide each side by '3'.
n = -3.666666667

Simplifying
n = -3.666666667

See similar equations:

| 5(x+2)-3(x-4)=7-x | | 8-7p=12-5p | | Y=sec(x^3) | | 8y+43-7y=75 | | 4c-5(x+1)+11=0 | | Y=3tan*4x | | x+(x*.0875)=20.12 | | 5(2x-7)=0 | | 2y+x=8.5 | | 2x^3+10x^2-2x-10=0 | | 6x+29=65 | | 4x=-2x-42 | | 3x+2.5=4x-35 | | 4(2-2y)+6=2(7+4y) | | 18x-3y=6 | | 2+2m=4m+5 | | -3x+3/5+1/5=2(4-x)/5 | | -13-(3m+4)= | | (1-u)(2u-7)=0 | | x-7=(2x-4) | | -9x+6y=72 | | 1-4j=2j | | Y=cos(3x) | | 8+2(3a-5)-(6a-8b*b)-4b*b= | | 8x+4y=-56 | | 5x^2+18x-8=0 | | 2.5x+15+0.5(x-4)=1.2x+2(0.5x-6) | | 4(2y+9)+7y= | | 7(x+2)=7x+2 | | (5x+3-2)(8-2x+1)= | | 9-.333g=13 | | 2x^2+9x=5 |

Equations solver categories